Forecasting Carbon Emission Reductions: The Role of Solar Energy in Substituting Coal for Sustainable Development Goals - Aimon, Hasdi; Kurniadi, Anggi Putri; Sentosa, Sri Ulfa; Yahya, Yahya; Rahman, Nurhayati Abd (International Journal of Energy Economics and Policy, 2024)
This research aligns with the Sustainable Development Goals (SDGs), particularly SDG 7 (affordable and clean energy) and SDG 13 (climate action), by introducing a comprehensive model for carbon emissions reduction through the substitution of clean energy to achieve the SDGs. The analysis begins with panel regression using historical data from 2008 to 2023, focusing on selected countries in the Asia-Pacific region, including coal-exporting countries like Indonesia and Australia, as well as coal-importing countries like China. The analysis is then extended with an ARIMA approach to forecast coal and solar energy consumption for the period 2024-2030. Subsequently, the forecast for carbon emissions reduction is conducted on average, analyzed using the previous panel regression equation by introducing values from the ARIMA analysis into pessimistic, moderate, and optimistic categories. The findings of this study indicate that solar energy consumption plays a crucial role in reducing carbon emissions, while coal consumption increases carbon emissions. On the other hand, the optimistic approach can facilitate the dominance of solar energy in the overall energy mix, resulting in significantly lower carbon emissions growth rates. Therefore, this research emphasizes the need to implement an optimistic model to drive the achievement of SDG 7 and SDG 13 by 2030.